Pengembangan Komik Digital Sebagai Media Pendidikan Moderasi Beragama Berbasis Teks Susastra Hindu di Kota Denpasar - Agus Triadi Kiswara, Komang (Jayapangus Press, 2025)
The aim of this research is to develop religious moderation educational media based on Hindu literary texts in Denpasar City. The teachings of Hinduism, which are universal and constitute the majority of its adherents in the city of Denpasar, must of course be able to become role models in developing an attitude of moderation. The current weakness is the moderation discourse which is still felt to be exclusive, as well as the lack of moderation learning media that is interesting to the general public. Based on this problem, it is important to develop a media moderation in the form of digital comics. The methodology in this research uses the triagjhan 4D development research methodology with the development flow of Define, Design, Develop, and Disseminate. The research results show that the value of religious moderation in Hindu literary texts is in line with the components of religious moderation. The development of religious moderation comics at the define stage found a lack of public understanding about religious moderation. Design stage (designing) preparation of test standards, media selection, material format selection. The validation results from media experts show a percentage of 96.92%, which means it is very feasible, validation from material experts with a percentage of 84.61%, meaning it is very feasible, user testing shows a score of 84.8%, meaning it is very feasible, so this comic can be said to be very feasible. Dissemate (spreading) where the dissemination stage is carried out using QR Code media in the catus pata field in Denpasar City. The effectiveness of using comics where comics are effective in supporting religious moderation material based on Hindu literary texts so that they are easy to learn. The conclusion is that religious moderation education must always be improved through various media, one of which is digital comic media. The results of the development of digital comic educational media based on Hindu literary texts show that digital comics are very suitable for use as a medium for religious moderation education in Denpasar City.